Liturgical transformation of Diocesan Church in Palangkaraya, Indonesia - Fransiskus J. Hamu; Adison A. Sihombing; Zaenuddin H. Prasojo; Emanuel P.D. Martasudjita; Antonius D. Firmanto (HTS Teologiese Studies/Theological Studies, 2023)
The congregation is challenged by modern times that require various life adjustments, including priestly pastoral ministry. Therefore, this study examined the pastoral ministry style for the parishioner’s rural community of St. Petrus Paulus Ampah Diocese in Palangka Raya. A descriptive qualitative approach was used with data collected using participatory observations, in-depth interviews and document studies. Furthermore, the data analysis involved reducing, displaying and process verification. The participants included parish priests, catechists and station council administrators. The results showed that the congregations did not participate in church activities because the pastoral ministry style did not fulfil their needs, economic factors and lack of Catholic faith knowledge. Therefore, the church authorities in pastoral ministry should create a holistic and transformative congregation based on their needs. The current pastoral ministry practice is based on ecclesiastical organisation building and worship (liturgy) focused service. The church should simultaneously conduct catechism practices and charitable diaconia such as social, economic and spiritual activities. This was an interdisciplinary study that focused on practical and pastoral theology, catechesis and social sciences on Catholics’ pastoral ministry style for rural communities.